Determinación de la eficiencia productiva a la aplicación de 3 dosis de biol y humus en el cultivo de lechuga (Lactuca sativa L) variedad red king en Laguacoto II, provincia de Bolívar - Ramírez Iza, Nancy Yessenia (2023)
Determination of the productive efficiency to the application of 3 doses of biol and humus in the cultivation of lettuce (Lactuca sativa L) variety red King in Laguacoto II, province of Bolívar. In the present investigation the following objectives were raised: Identify the organic fertilizer that generates the greatest increase in the productivity of the lettuce crop. Determine the optimal dose of biol and humus for the agronomic and productive development of the lettuce crop Evaluate the agronomic and productive behavior of the lettuce crop in the application of the different treatments Carry out an economic analysis of the B/C relationship; for which 1260 lettuce seedlings and organic fertilizers were used: Biol, humus. The design was of the experimental type with randomized complete blocks (DBCA), in 3 repetitions; Tukey's test at 5% was performed to compare treatment averages and regression analysis and simple correlation. The main conclusions were: The highest yield of Red King variety lettuce was obtained with worm humus fertilizer in a contribution of 31 Tm/ha (T1), obtaining 16,432.75 Kg/ha. Regarding the biol applied to the crop, the most representative yield was registered in the dose of 2 741.2 liters/ha, averaging a weight of 8 925.44 Kg/ha. Yield was reduced by 42% as a result of late-harvest treatments. The best treatment from the economic point of view was T1, with net benefits of $393.01 per hectare, the highest RB/C of $1.06 USD and an RI/C of 0.06 USD.